2022
DOI: 10.1007/s10067-022-06126-x
|View full text |Cite
|
Sign up to set email alerts
|

Systemic lupus erythematous after Pfizer COVID-19 vaccine: a case report

Abstract: The Pfizer-BioNTech COVID-19 vaccine has been authorized by the U.S. Food and Drug Administration as it demonstrated 95% effectiveness against the SARS-CoV-2 virus. Although the initial vaccine trials showed a favorable side effect profile, there have been concerns regarding activation of aberrant immune responses, triggering autoimmunity. This is a case report of a 68-year-old woman without history of autoimmune conditions, who presented to our emergency department 7 days after receiving the Pfizer-BioNTech C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
21
1
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(23 citation statements)
references
References 25 publications
(21 reference statements)
0
21
1
1
Order By: Relevance
“…The adverse events were negligible and there were no severe adverse events in both groups of SLE cases and healthy individuals after SARS-CoV-2 inactivated vaccine (31). This is in sharp contrast to other mentioned reports with increased side effects and flares with use of mRNA COVID-19 vaccines such as Pfizer/BioNTech (BNT162b2) (12)(13)(14)17,18,(20)(21)(22)(23)25,26), AZD1222 vaccine (15,16) and Moderna (19,24).…”
Section: Antibody Response Following Covid-19 Vaccination In Covid-19...contrasting
confidence: 60%
See 1 more Smart Citation
“…The adverse events were negligible and there were no severe adverse events in both groups of SLE cases and healthy individuals after SARS-CoV-2 inactivated vaccine (31). This is in sharp contrast to other mentioned reports with increased side effects and flares with use of mRNA COVID-19 vaccines such as Pfizer/BioNTech (BNT162b2) (12)(13)(14)17,18,(20)(21)(22)(23)25,26), AZD1222 vaccine (15,16) and Moderna (19,24).…”
Section: Antibody Response Following Covid-19 Vaccination In Covid-19...contrasting
confidence: 60%
“…Lemoine et al reported an SLE patient presenting with inflammatory arthritis, positive ANA and elevated dsDNA in a 68-year-old woman without previous history of autoimmune diseases, around seven days following receiving the first dose of the Pfizer-BioNTech COVID-19 vaccine. This patient recovered significantly after the use of steroids (22).…”
Section: Review Of Published Cases Of Sle or Sle-like Syndromes Follo...mentioning
confidence: 76%
“…Kanduc et al examined peptide sharing between the SARS-CoV-2 spike protein and human proteins and discovered significant sharing at the heptapeptide level [ 19 ] suggesting that antibodies produced in response to the vaccine may cross-react with the host and cause autoimmune diseases in susceptible individuals [ 20 ]. Following mRNA vaccination, various pro-inflammatory pathways are triggered as a result of the mRNA itself, liposomes or lipid nanoparticles used to encapsulate the mRNA, and receptor binding essential for spike protein translation [ 21 ].…”
Section: Introductionmentioning
confidence: 99%
“…Little is known about COVID-19 vaccination in patients with autoimmune skin diseases; however, cases of onset and exacerbation of cutaneous and systemic lupus erythematosus have been reported following the use of immunizers. 1 , 2 , 3 , 4 , 5 , 6 , 7 , 8 , 9 This report describes a chronic cutaneous lupus erythematosus (CCLE) exacerbation thirty days after the second dose of ChAdOx1 nCoV-19 vaccine (Oxford/AstraZeneca).…”
mentioning
confidence: 99%
“… 3 The onset or exacerbation of lupus after vaccination is rare, with few cases in the literature. 1 , 2 , 3 , 4 , 5 , 6 , 7 , 8 , 9 The international VACOLUP study indicated that COVID-19 vaccine was well tolerated in patients with systemic lupus erythematosus. Among the 696 participants assessed, only 3% reported a medically confirmed SLE flare after the immunization.…”
mentioning
confidence: 99%